Strategi Bauran Pemasaran Dalam Pengembangan Usaha Dengan Metode PLC (Product Life Cycle) - Lisa Sulistyawati; Hasna Wijanarko (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Business is an activity carried out to earn profits and fulfill daily needs, both activities carried out daily or activities in the business sector or buying and selling activities of a product. Clothing is included in one of the primary needs, a designation commonly known as clothing needs which are also important for humans. In addition, this makes clothes mainly clothes to be one of the types of fashion that has the fastest development because many people need clothes more than other types of fashion such as bags, shoes or others. Thriftshop “Projectnine” at Simo Sidomulyo Baru No. 29 A Surabaya is one example of the many thriftshop businesses that are currently booming, because they are considered easy to run, have a low risk of failure and the initial capital is not too large. The large number of similar competitors that exist makes business development important for Thriftshop "Projectnine". Business development carried out, especially planning in the long term, is very important for any existing business or business so that the business has an increasing and better value in terms of sales, systems and others. Developments that occur in an increasingly competitive business world require every business actor to have the right business strategy, for example a good marketing strategy can make the business or business achieve the planned or determined growth rate. Therefore, in determining the marketing strategy, the company must know the stages of a product in the product life cycle with the aim that the company can take a better and appropriate marketing plan or strategy policy, this information can be known by applying the product life cycle method. From the results of calculations and determining the stages of the product life cycle using the Polli and Cook method, it was found that the "Projectnine" thriftshop clothing product was in a growth stage where the "Projectnine" thriftshop business experienced an increase in sales and was followed by increased profits and market competition so that the strategy the marketing mix at this stage affects the development of the "Projectnine" thriftshop business. Keywords: Business development, product life cycle, thriftshop